2022
DOI: 10.1101/2022.11.10.515773
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Does the visual word form area split in bilingual readers? A millimeter-scale 7T fMRI study

Abstract: In expert readers, a brain region known as the visual word form area (VWFA) is highly sensitive to written words, exhibiting a posterior-to-anterior gradient of increasing sensitivity to orthographic stimuli whose statistics match those of real words. Using high-resolution 7T fMRI, we ask whether, in bilingual readers, distinct cortical patches specialize for different languages. In 21 English-French bilinguals, unsmoothed 1.2 mm fMRI revealed that the VWFA is actually composed of several small cortical patche… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 125 publications
(199 reference statements)
1
4
0
Order By: Relevance
“…These results are in line with previous observations of similar coding principles for linguistic properties implemented within different sub-populations of VWFA for separate scripts (Lerma-Usabiaga et al, 2018; Yeatman & White, 2021; Zhan et al, 2023). In bilinguals, high similarity was present in activated neural populations between French and English, but less so between French and Chinese (Zhan et al, 2023). However, bilinguals might activate sounds with the two scripts.…”
Section: Discussionsupporting
confidence: 92%
“…These results are in line with previous observations of similar coding principles for linguistic properties implemented within different sub-populations of VWFA for separate scripts (Lerma-Usabiaga et al, 2018; Yeatman & White, 2021; Zhan et al, 2023). In bilinguals, high similarity was present in activated neural populations between French and English, but less so between French and Chinese (Zhan et al, 2023). However, bilinguals might activate sounds with the two scripts.…”
Section: Discussionsupporting
confidence: 92%
“…In light of these findings, we interpret our results as attesting to the different levels of analysis that are carried out in each subregion of the VWFA. Several studies have reported a hierarchy in the VTC, where sensitivity to lexical features and abstract language information increases along the posterior–anterior axis (Binder et al, 2006; Olulade et al, 2015; Taylor et al, 2019; van der Mark et al, 2009; Vinckier et al, 2007; Zhan et al, 2023). Interestingly, a recent review found that studies that compare responses to text with responses to non‐text stimuli, typically reveal text‐selective activations in a wide range of locations along the posterior–anterior axis.…”
Section: Discussionmentioning
confidence: 99%
“…In the visual domain, there are mixed findings regarding the functional properties of this region, specifically debates center around the degree of selectivity it shows to language content compared with low‐level visual features of text (Caffarra et al, 2021; Dehaene & Cohen, 2011; Vogel et al, 2014; Yeatman & White, 2021) or other visual stimuli (Centanni et al, 2017; Hervais‐Adelman et al, 2019; Kubota et al, 2019; Song et al, 2012). Recent evidence suggests that these inconsistencies indicate that the VWFA is not a single, uniform, region, but comprises a series of subregions that differ in the level of computation they perform on the textual input (Lerma‐Usabiaga et al, 2018; White et al, 2019; Yeatman & White, 2021; Zhan et al, 2023). Specifically, the more posterior patch, VWFA‐1, is sensitive to visual letter‐shapes and orthographic information, while the more anterior VWFA‐2 is sensitive to the language content of the visual text.…”
Section: Introductionmentioning
confidence: 99%
“…These orthographic responses are thought to subserve major aspects of typical reading behavior 3,7 . Further, this region is lateralized to the left 8,9 and in approximately the same location across individuals, different languages (English vs. French) 10 , and even different writing systems (alphabetic vs. logographic) 11 . Thus, the VWFA is vastly studied as a prime example of how the human brain has the capacity to dedicate cortical tissue for new symbolic representations.…”
Section: Introductionmentioning
confidence: 92%
“…Second, although located in approximately the same location across individuals, the VWFA is a small region, and the exact location varies from person to person 33 . Relying on group activation or using anatomical coordinates (on a template brain) may not capture word-selective voxels because they do not account for individual variability and/or because they assume a continuous cluster (as with a spherical ROI) which is not a prerequisite for category-selective regions 10,34 . Third, the VWFA is adjacent to many other category-selective regions within the VTC; therefore, to understand the unique function and neural signature of the VWFA, it is also necessary to define as many of these other regions as possible within each individual and test neural preferences of each region across different stimulus conditions.…”
Section: Introductionmentioning
confidence: 99%